Human Papillomavirus-induced Cutaneous and Mucosal Lesions in a Patient with Rothmund-Thomson Syndrome - Thomas Kuntz; Bijan Koushk-Jalali; Christian Tigges; Steffi Silling; Frank Oellig; Cristina Has; Monika Hampl; Ulrike Wieland; Alexander Kreuter (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)